Principles & practice of urology a comprehensive text - Salam, M. A. (Muhammad Abdus), 1951- (Brown Walker Press, 2003)
Principles and Practice of Urology was created to provide a fresh, practical and concise review of the important urological issues faced in the daily practice. An easy and simple style is used to discuss the different urological diseases. This comprehensive and compact presentation serves the undergraduate and postgraduate medical student as a text book while providing a rapid review of the subject with reference work for the experienced professional, including General Surgeons, gynecologists, oncologist, neurologists, neurosurgeons, pediatric surgeons, spinal surgeons, nephrologists and physicians.